Administrative and legal regulation of the activities of tax authorities in Ukraine regarding the implementation of administrative procedures - Mentukh , Nataliіa (Actual problems of law (Aktual'ni problemi pravoznavstva), 2025)
The article is devoted to the definition of the concept and features of administrative and legal regulation of the activities of tax authorities in Ukraine regarding the implementation of administrative procedures based on the consideration and analysis of theoretical foundations.It is substantiated that the legal aspects of the implementation of administrative procedures by tax authorities are enshrined in a number of regulatory legal acts that differ both in their legal force and in the degree of definition of administrative and legal regulation of the implementation of administrative procedures by tax authorities.The scientific positions on the concept of "administrative procedures" are analyzed, on the basis of which it is determined that in Ukrainian legal doctrine administrative procedures are usually understood as an established procedure for the implementation of the rights and obligations of individuals and legal entities in executive bodies and executive bodies of local self-government.It is argued that an administrative procedure is a normatively established unified procedure for the implementation of activities by an administrative body aimed at limiting administrative discretion when the body exercises discretionary powers in relations with citizens and legal entities in the form established by law.It is noted that to ensure the proper functioning of the state tax system, the legal aspects of the implementation of administrative procedures by tax authorities are of great importance, which is why their legal support should be determined at the law level.Аdministrative procedure is a system of administrative and procedural norms that determine the order of actions of public administration bodies (administrative bodies).Based on the analysis of theoretical principles and norms of current legislation, the author provides a definition of administrative and legal regulation of the activities of tax authorities regarding the implementation of administrative procedures, and also highlights the implementation of certain measures regarding the implementation of administrative procedures by tax authorities.